2018
DOI: 10.1038/s41598-018-34316-8
|View full text |Cite
|
Sign up to set email alerts
|

Postprandial glycaemia-lowering effect of a green tea cultivar Sunrouge and cultivar-specific metabolic profiling for determining bioactivity-related ingredients

Abstract: Although the major green tea catechins can inhibit the activity of carbohydrate-hydrolyzing enzymes, there is a paucity of information describing the potential of other green tea ingredients and numerous green tea cultivars. Herein, we reveled that a green tea cultivar Sunrouge significantly suppressed the postprandial blood glucose level in mice. Unlike the most representative Japanese green tea cultivar, Yabukita, the suppression by Sunrouge was observed clearly during the initial period after oral dosing of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 26 publications
0
23
0
Order By: Relevance
“…AChE is exists in all excitable cells, while BChE enzyme is present more commonly in the central neural system, plasma, and liver (Gulçin et al, 2017). Inhibition of the carbohydrate digestion enzymes such as α-glycosidase and α-amylase can cause to reduction of postprandial blood glucose level when fed with a high-carbohydrate diet (Wasai et al, 2018). Therefore, it can be an important strategy for the management of postprandial blood glucose level in type 2 DM as well as borderline patients.…”
Section: Inhibition Of Ache and Bche Enzymes Which Hydrolysis Ach Andmentioning
confidence: 99%
“…AChE is exists in all excitable cells, while BChE enzyme is present more commonly in the central neural system, plasma, and liver (Gulçin et al, 2017). Inhibition of the carbohydrate digestion enzymes such as α-glycosidase and α-amylase can cause to reduction of postprandial blood glucose level when fed with a high-carbohydrate diet (Wasai et al, 2018). Therefore, it can be an important strategy for the management of postprandial blood glucose level in type 2 DM as well as borderline patients.…”
Section: Inhibition Of Ache and Bche Enzymes Which Hydrolysis Ach Andmentioning
confidence: 99%
“…Green tea catechins have been found to lower the level of postprandial blood glucose in mice after dosing of starch. , A retrospective cohort analysis showed that a reduced risk of type 2 diabetes was associated with the consumption of green tea . Recently, we reported that green tea extract (GTE) derived from the representative Japanese tea cultivar has an inhibitory effect on elevated blood glucose levels in mice . DPP-IV inhibitory activity was found in GTE derived from one of Bangladesh tea cultivars. , In addition, this activity was also reported in epigallocatechin-3- O -gallate (EGCG), the major green tea catechin .…”
Section: Introductionmentioning
confidence: 94%
“…A current research provided the possibility that food-derived phenolic compounds could cause a delay of glucose absorption by inhibiting carbohydrate-hydrolyzing enzymes such as α-glucosidase and α-amylase, which would in turn reduce the level of postprandial blood glucose. It appears to be an appropriate strategy for treating and preventing type 2 diabetes. Incretins, both glucagon-like peptide-1 (GLP-1) and glucose-dependent insulinotropic polypeptide, are representative peptide hormones secreted from enteroendocrine cells in the gastrointestinal tract after food intake. , In healthy individuals, incretin action is responsible for 60–70% of the secretion of postprandial insulin in response to glucose . However, secreted incretins are short-lived because they are rapidly degraded, and their level and effectiveness are markedly reduced, especially in patients with type 2 diabetes .…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, epicatechin-3- O -(3- O -methyl) gallate (ECG3”Me), epigallocatechin-3- O -(3- O -methyl) gallate (EGCG3”Me), EGCG, and epicatechin-3- O -gallate (ECG) inhibited α-glucosidase, and in this case EGCG3”Me had the strongest effect. Their IC 50 values were 14.7, 8.1, 13.3, and 61.1 µM respectively [ 21 ]. C was also shown to inhibit α-glucosidase stronger than acarbose (IC 50 = 87.55 µg/mL vs. 199.53 ± 1.12 μg/mL, respectively) [ 22 ].…”
Section: Antidiabetic Effects Of Flavan-3-ols: In Vitro and In Vivmentioning
confidence: 99%
“…[40] [21]. C was also shown to inhibit α-glucosidase stronger than acarbose (IC 50 = 87.55 µg/mL vs. 199.53 ± 1.12 µg/mL, respectively) [22].…”
Section: Insulin Signaling Pathways and Glucose Peripheral Uptakementioning
confidence: 99%